The HR executive effect on firm performance and survival - Chadwick, Clint; Guthrie, James P.; Xing, Xuejing (Strategic Management Journal, 2016)
Research summary : This article replicates and extends Welbourne and Cyr's (1999) pioneering study of the relationship between the presence of human resource executives (HREs) and firm performance in initial public offering (IPO) firms. We employ a larger, more generalizable sample, a model better fitted to the IPO context, and alternative performance measures to execute a more robust examination of this relationship. Using Welbourne and Cyr's model specifications, our results parallel theirs: there is no significant relationship between HREs and firms' post‐IPO financial performance. Moreover, extending Welbourne and Cyr's study, we find that the presence of HREs at the time of firms' IPOs is positively related to the ultimate success measure: post‐IPO firm survival. Additionally, for firms that had executives at the time of IPO, the negative effect of firm size on firm mortality is greater and the positive effect of leverage on firm mortality is smaller. Managerial summary : Does paying attention to HRM help firms to succeed? This study examines that question in a sample of generally small, young firms that went public from 1996 to 2008. Only about 10 percent of these firms had human resource executives (HREs) at the time of their IPOs, allowing us to examine the effects of the presence of HREs on firm performance. While we find that the presence of an HRE at IPO is not related to firms' post‐IPO financial performance, firms that had HREs at IPO are significantly more likely to survive in the long run. Since approximately 20 percent of the sample firms do not survive, this is a very meaningful outcome. Indeed, survival may be the ultimate measure of firm performance . Copyright © 2016 John Wiley & Sons, Ltd.